2002
DOI: 10.1080/10889860290777440
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of a PAH Mixture by Native Subsurface Microbiota

Abstract: Laboratory microcosm studies were conducted to estimate biodegradation rates for a mixture of five polycyclic aromatic hydrocarbon compounds (PAHs). Static microcosms were assembled using soil samples from two locations collected at a No. 2 fuel oil-contaminated site in the Atlantic Coastal Plain of Virginia. In microcosms from one location, five PAHs (acenaphthene, fluorene, phenanthrene, pyrene, and benzo(b)fluoranthene) biodegraded at net first-order rates of 1.08, 1.45, 1.13, 1.11, and 1.12 yr -1 , respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…[1,2] PAS are also considered carcinogenic and mutagenic due to their similarity with PAHs. [5] However, PAHs and heterocyclic PAS remain in soil, [6] especially in weathered soils. [4] On the other hand, remediation of contaminated soils with hydrocarbons, has lower operation costs with biological processes than with physico-chemical methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] PAS are also considered carcinogenic and mutagenic due to their similarity with PAHs. [5] However, PAHs and heterocyclic PAS remain in soil, [6] especially in weathered soils. [4] On the other hand, remediation of contaminated soils with hydrocarbons, has lower operation costs with biological processes than with physico-chemical methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Finally it is worth noting that the first-order degradation rates used in the model to best fit the field data are achieved assuming values that are in line with those reported in the literature (e.g. Davis et al, 2009;DeVaull et al, 1997;Brauner et al, 2002;Blum et al, 2009;Bockelmann et al, 2001). Namely, as discussed before, typical average median values of biodegradation constant rates for BTEX are in the order of 0.01 and 10 d À1 whereas for PAHs are in the range of 0.0001e0.01 d À1 .…”
Section: Attenuation During Leachingmentioning
confidence: 92%
“…Typical biodegradation rate constants values available in literature for these compounds are in the range of 0.0001e0.01 d À1 (e.g. see Brauner et al, 2002;Blum et al, 2009;Bockelmann et al, 2001).…”
Section: Risk Calculationmentioning
confidence: 99%
“…One example of how this half-cell reaction approach was applied to quantifying electron acceptor utilization of PAH compounds is presented in Brauner et al (2002).…”
Section: A432 Stoichiometric Estimates Of Biodegradation Effectsmentioning
confidence: 99%
“…In addition, actual electron acceptor requirements may vary from those predicted by the stoichiometric relationships presented above because metabolic activity by the microbial population will use a portion of the biodegraded hydrocarbon for cell growth. Grady et al (1999) demonstrated that stoichiometric formulations could be modified to account for microbial growth by 1) assuming that a portion of the growth substate (i.e., hydrocarbon) was converted into biomass and 2) accounting for this biomass production as a reaction endproduct using the empirical formula C 5 H 7 O 2 N. Using this approach, and a bacterial yield coefficient (Y m ) that describes the amount of biomass produced per unit mass of substrate biodegraded (Grady et al, 1999), Brauner et al (2002) describe a process by which biomass production can be accounted for when using stoichiometric calculations for evaluating hydrocarbon degradation and associated electron acceptor utilization. Yields of microbial biomass vary depending on the thermodynamics of substrate biodegradation and on the availability of electron acceptor, nutrients, and substrate concentration (McCarty, 1971).…”
Section: A432 Stoichiometric Estimates Of Biodegradation Effectsmentioning
confidence: 99%